Validation of the Adherence Determinants Questionnaire scale among women with breast and cervical cancer - Paula Renata Amorim Lessa; Samila Gomes Ribeiro; Priscila de Souza Aquino; Paulo Cesar de Almeida; Ana Karina Bezerra Pinheiro (Universidade de São Paulo, 2015)
Objectives: the aim was to translate and culturally adapt the Adherence Determinants Questionnaire scale for the Portuguese language in the Brazilian context, and to check its reliability and validity to analyze the elements of the adherence of patients to the clinical treatment for breast and cervical cancer.Method: this was a methodological study, carried out in two oncology reference centers. The sample consisted of 198 participants, with 152 being treated for breast cancer and 46 being treated for cervical cancer. The content validation was performed by a committee of experts. The construct validation was demonstrated through factor analysis and the reliability was analyzed using Cronbach's alpha.Results: the committee of experts made the necessary adjustments so that the scale was adapted to the Brazilian context. The factor analysis suggested a reduction from seven to five factors and the maintenance of 38 items similar to those of the original scale. The reliability, investigated through Cronbach's alpha, was .829, showing high internal consistency.Conclusion: it was concluded that the Brazilian version of the Adherence Determinants Questionnaire scale is a valid and reliable instrument that is able to measure the elements of adherence to the treatment for breast and cervical cancer.